Liposomal Delivery of Mitoxantrone and a Cholesteryl Indoximod Prodrug Provides Effective Chemo-Immunotherapy in Multiple Solid Tumors - Mei, Kuo-Ching (ACS Nano, 2020)
We developed a custom-designed liposome carrier for co-delivery of a potent immunogenic cell death (ICD) stimulus plus an inhibitor of the indoleamine 2,3-dioxygenase (IDO-1) pathway to establish a chemo-immunotherapy approach for solid tumors in syngeneic mice. The carrier was constructed by remote import of the anthraquinone chemotherapeutic agent, mitoxantrone (MTO), into the liposomes, which were further endowed with a cholesterol-conjugated indoximod (IND) prodrug in the lipid bilayer. For proof-of-principle testing, we used IV injection of the MTO/IND liposome in a CT26 colon cancer model to demonstrate the generation of a robust immune response, characterized by the appearance of ICD markers (CRT and HMGB-1) as well as evidence of cytotoxic cancer cell death, mediated by perforin and granzyme B. Noteworthy, the cytotoxic effects involved natural killer (NK), which suggests a novel type of ICD response. The immunotherapy response was significantly augmented by co-delivery of the IND prodrug, which induced additional CRT expression, reduced number of Foxp3(+) Treg and increased perforin release, in addition to extending animal survival beyond the effect of an MTO-only liposome. The outcome reflects the improved pharmacokinetics of MTO delivery to the cancer site by the carrier. In light of the success in the CT26 model, we also assessed the platform efficacy in further breast cancer (EMT6 and 4T1) and renal cancer (RENCA) models, which overexpress IDO-1. Encapsulated MTO delivery was highly effective for inducing chemo-immunotherapy responses, with NK participation, in all tumor models. Moreover, the growth inhibitory effect of MTO was enhanced by IND co-delivery in EMT6 and 4T1 tumors. All considered, our data support the use of encapsulated MTO delivery for chemo-immunotherapy, with the possibility to boost the immune response by co-delivery of an IDO-1 pathway inhibitor.